2015
DOI: 10.1080/1068316x.2015.1054389
|View full text |Cite
|
Sign up to set email alerts
|

Problems in expert deception detection and the risk of false confessions: no proof to the contrary in Levine et al. (2014)

Abstract: Lie detection research has shown that observers who rely on nonverbal cues or on verbal cues correctly classify on average 54% of truth tellers and liars. In addition, over the years, countless numbers of innocent people have made false confessions and, in analysing the problem, researchers have implicated both a suspect's vulnerability and the persuasive influence of certain police interrogation tactics. Levine et al. (2014) aim to contribute to these vast bodies of literature by reporting two studies purport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…We agree with Vrij et al (2015) that research prior to 2006 documents that accuracy in deception detection experiments is approximately 54% plus or minus 10%, and that past research has found that experts perform similarly to students. This was explicit in the literature review of our 2014 paper.…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…We agree with Vrij et al (2015) that research prior to 2006 documents that accuracy in deception detection experiments is approximately 54% plus or minus 10%, and that past research has found that experts perform similarly to students. This was explicit in the literature review of our 2014 paper.…”
Section: Introductionsupporting
confidence: 77%
“…On face, our findings appear to contradict the findings and claims of our critics' programs of research. Our critics (Vrij et al, 2015) would have readers believe that their own findings are unassailable and our findings are pure artifact easily dismissed as unscientific.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations